The Implementation of Task – Based language Teaching in Teaching English Speaking - Liza Kurnia Abati (Journal of English Education Program (JEEP), 2017)
This research investigated the implementation of Task – based language teaching in teaching English speaking. It was aimed to know how the teacher implement Task – based language teaching in teaching English speaking, and what is student’s perception on the implementation of Task – based Language Teaching in teaching English speaking. there are three stages in Task – Based Language Teaching such as; pre – task, task – cycle, and language focus or post – task. During the teaching and learning process all of the students had to use English language as well as possible, without being stuck on the use of grammar. In task – based language teaching the use of grammatical structure is less active. This enabled the students feel more confident to speak English in front of their friends, Besides, it gave them a great motivation to learn English. Based on these findings, it is recommended that task – based language teaching cab be applied in teaching speaking. In order to make teaching and learning process more comfortable and enjoyable.Keywords : Task – Based Langauge Teaching, Teaching speaking.